The Influence of Work Environment, Performance Appraisal, and Work Discipline on Employee Work Productivity in Tlogomas Village, Malang City - Setyaningrum, Fitria; Hidayat , Imam (International Research and Development for Human Beings (IRDH), 2025)
Organizational development in Indonesia is approaching a modern organization, where one element is connected to another. This study aims to determine the influence of the environment, performance appraisal, work discipline, work performance on employee work productivity, at the Tlogomas Village Office, Malang City. The research method uses multiple linear regression analysis with a saturated sampling technique of 32 employees at the Tlogomas Village Office, Malang City. The results of the study indicate that the work environment, performance appraisal and work discipline simultaneously (together) have a positive and significant effect on employee work productivity at the Tlogomas Village Office, Malang City.